UBXD4, a UBX-Containing Protein, Regulates the Cell Surface Number and Stability of α3-Containing Nicotinic Acetylcholine Receptors - Rezvani, Khosrow (Society for Neuroscience, 2009)
Adaptor proteins are likely to modulate spatially and temporally the trafficking of a number of membrane proteins, including neuronal nicotinic acetylcholine receptors (nAChRs). A yeast two-hybrid screen identified a novel UBX-containing protein, UBXD4, as one of the cytosolic proteins that interact directly with the α3 and α4 nAChR subunits. The function of UBX-containing proteins is largely unknown. Immunoprecipitation and confocal microscopy confirmed the interaction of UBXD4 with α3-containing nAChRs (α3* nAChRs) expressed in HEK293 cells, PC12 cells, and rat cortical neurons. Overexpression of UBXD4 in differentiated PC12 cells (dPC12) increased nAChR cell surface expression, especially that of the α3β2 subtype. These findings were corroborated by electrophysiology, immunofluorescent staining, and biotinylation of surface receptors. Silencing of UBXD4 led to a significant reduction of α3* nAChRs in rat cortical neurons and dPC12 cells. Biochemical and immunofluorescence studies of endogenous UBXD4 showed that the protein is located in both the ER and cis-Golgi compartments. Our investigations also showed that the α3 subunit is ubiquitinated and that UBXD4 can interfere with its ubiquitination and consequent degradation by the proteasome. Our data suggest that UBXD4 modulates the distribution of α3* nAChRs between specialized intracellular compartments and the plasma membrane. This effect is achieved by controlling the stability of the α3 subunit and, consequently, the number of receptors at the cell surface.